2013
DOI: 10.12776/amsc.v3i0.102
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SLAB PULLING RATE ON FRACTURE CHARACTERISTICS AND NOTCH IMPACT TOUGHNESS OF SLAB SURFACE ZONE IN Ti-Nb MICROALLOYED STEEL

Abstract: The paper analyzes the marginal cut-outs from two slabs of Ti-Nb microalloyed steel. The first slab was transitional with initial pulling rate 0.5 m.min -1 and final pulling rate 0.8 m.min -1 . The second slab was cast at real pulling rate 1.03 m.min -1 . The V-notch Charpy impact test showed that at low pulling rate 0.5 m.min -1 , the values of impact toughness (KCV) were higher than those at high slab pulling rates. When the pulling rate was 0.5 m.min -1 , mixed fractures were obtained, occasionally ductile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Non-equilibrium microstructure observed in the marginal cut-outs arises due to increased heat dissipation. In works [9,12] it was confirmed that not only the slab cooling rate has an impact on formation of non-equilibrium microstructure, but also the slab pulling rate. The presence of coarse-grained microstructure indicative of coarse-grained original austenitic grain and larger austenite grain also promotes the formation of non-equilibrium microstructure.…”
Section: Comat 2014 -Recent Trends In Structural Materialsmentioning
confidence: 91%
“…Non-equilibrium microstructure observed in the marginal cut-outs arises due to increased heat dissipation. In works [9,12] it was confirmed that not only the slab cooling rate has an impact on formation of non-equilibrium microstructure, but also the slab pulling rate. The presence of coarse-grained microstructure indicative of coarse-grained original austenitic grain and larger austenite grain also promotes the formation of non-equilibrium microstructure.…”
Section: Comat 2014 -Recent Trends In Structural Materialsmentioning
confidence: 91%
“…It has been shown that the impact toughness of cast semis depends similarly as in forgings [2] on the external conditions of the Charpy impact test, on the chemical composition of the steel and on the microstructure of the material [3]. Moreover, it also depends on the casting technology, including the pulling rate of the slab [4], cooling rate, presence of oscillation marks (OM), and inclusions. In work [5] the influence of test piece thickness on the evaluated toughness was analyzed at room temperature for different kinds of steels continuously-cast slab surface zones.…”
Section: Introductionmentioning
confidence: 99%